Recurrent Abdominal Pain and Weight Loss in an Adolescent: Celiac Artery Compression Syndrome. (2010) - Gander, Sarah; Mulder, Daniel J; Jones, Sarah; Ricketts, John D; Soboleski, Don A; Justinich, Christopher J
Abstract : Celiac artery compression syndrome is a rare cause of abdominal pain and weight loss, likely caused by compression of the celiac artery or plexus by the median arcuate ligament. A case of celiac artery compression syndrome in a 17-year-old male patient with severe postprandial pain and weight loss is described. Imaging techniques such as computed tomography, angiography and Doppler ultrasound identified the abnormality, which was corrected by laparoscopic surgery.